Budgetary Planning and Budgetary Performance of Osukuru Town Council in Tororo District - Othieno Ephriam (Uganda Christian University, 2024)
This study examined the influence of budgetary planning on the budgetary performance of Osukuru Town Council in Tororo District. Utilizing a population of 45 and a sample of 40 respondents selected through the Slovin formula, the research aimed to assess the impacts of budget participation, coordination, and monitoring on budgetary outcomes. The findings revealed that budget participation had a moderate impact on performance, with a mean score of 3.03 (SD = 1.610) indicating that 33.3% of respondents agreed and 30.3% strongly disagreed on its effectiveness in improving performance. Budget coordination showed a similarly moderate effect, with a mean score of 3.42 (SD = 1.458) and 36.4% agreement, though its role in reducing duplication scored lower at 2.58 (SD = 1.521). Budget monitoring demonstrated a stronger influence, with a mean score of 2.76 (SD = 1.1045), suggesting a notable impact on financial reporting and adherence. The model summary for budget participation indicated an R value of 0.383 and an R-squared of 0.147, while budget coordination had an R value of 0.400 and an R-squared of 0.160, showing moderate relationships. Budget monitoring, with an R value of 0.694 and an R-squared of 0.481, highlighted a substantial impact. The study concluded that while budgetary planning components significantly influenced budgetary performance, their effectiveness varied. Recommendations included enhancing participatory processes, improving coordination practices, and strengthening monitoring mechanisms to boost overall budgetary performance.